Growth and functionalization of carbon nanotubes for nitroaromatic explosive detection. (2020) - Musayeva, N.; Orujov, T.; Hasanov, R.; Sultanov, Ch.; Ferrari, C.; Frigeri, C.; Trevisi, G.; Beretta, S.; Bosi, M.; Verucchi, R.; Aversa, L.; Sansone, F.; et al.
Abstract: This paper presents the synthesis and functionalization of carbon nanotubes (CNTs) with amino groups to prepare sensors for detecting explosives, in particular nitroaromatic explosives such as TNT. CNTs have been grown by aerosol-chemical vapor deposition (A-CVD) technique and analyzed by SEM, TEM Raman and IR spectroscopy methods. Very smooth and long CNTs with good electrical conductive properties have been obtained. Two steps of functionalization process have been performed, oxidation and amidation. Infrared absorption and elemental analysis confirmed the successful functionalization of the CNTs.